Hubungan Kualitas Pelayanan Dimensi Servqual dengan Loyalitas Pasien di Poliklinik RSUD Arosuka Tahun 2018 - Titen Yasril; Dachriyanus Dachriyanus; Harmawati Harmawati (Universitas Batanghari Jambi, 2019)
The lack of repeated visits of old patients will increase the cost of promotion to get new patients, one way to maintain old patients is to grow patient loyalty. Some patients in Arosuka General Hospital are still not loyal because they come to the hospital only for the first examination, then the patient goes to another hospital, some patients have not recommended the hospital to others, one of the factors that influence patient loyalty is the quality of service. This study aims to determine the relationship between service quality servqual dimensions and patient loyalty in Arosuka Hospital. The type of this study is cross sectional. The population in this study were all patients who came to the Arosuka Hospital polyclinic in 2018, a sample of 203 people with a proportional random sampling sampling technique conducted in April 2018 with the analysis used was the chi square test. The statistical test results obtained 60.1% of respondents not loyal, 61.6% of respondents stated that tangible was not good, 37.9% of respondents stated that reliability was not good, 51.2% of respondents stated that they were less responsive, 43.3% of respondents said assurace was not good, and 48.8% of respondents said empaty not good. There is a significant relationship between tangible, reliability, responsive, assurance, empathy and patient loyalty in Arosuka Hospital with a value of p <0.05 (p = 0.001, p = 0.015, p = 0.010, p = 0.002, p = 0.022). Tangible is the most dominant factor associated with patient loyalty. It is expected that the director will make a policy on service hours, sanctions for those who do not obey the service hours, coordinate with the local government in procuring transportation for patients, the head of the ward designing a comfortable waiting room, and providing suggestion boxes for patients.